Hepatitis B and hepatitis C in southeast and southern Asia: challenges for governments. (November 2016) - Wait, Suzanne; Kell, Emily; Hamid, Saeed; Muljono, David H; Sollano, Jose; Mohamed, Rosmawati; Shah, Samir; Mamun-Al-Mahtab,; Abbas, Zaigham; Johnston, Jennifer; Tanwandee, Tawesak; Wallace, Jack
Summary: In 2015, the Coalition to Eradicate Viral Hepatitis in Asia Pacific gathered leading hepatitis experts from Bangladesh, India, Indonesia, Malaysia, Pakistan, the Philippines, and Thailand to discuss common challenges to the burden posed by hepatitis B virus (HBV) and hepatitis C virus (HCV), to learn from each other's experience, and identify sustainable approaches. In this report, we summarise these discussions. Countries differ in their policy responses to HBV and HCV; however, substantial systemic, cultural, and financial barriers to achievement of elimination of these infections persist in all countries. Common challenges to elimination include limited availability of reliable epidemiological data; insufficient public awareness of risk factors and modes of transmission, leading to underdiagnosis; high rates of transmission through infected blood products, including in medical settings; limited access to care for people who inject drugs; prevailing stigma and discrimination against people infected with viral hepatitis; and financial barriers to treatment and care. Despite these challenges, promising examples of effective programmes, public–private initiatives, and other innovative approaches are evident in all countries we studied in Asia Pacific. The draft WHO Global Health Sector Strategy on Viral Hepatitis 2016–21 provides a solid framework upon which governments can build their local strategies towards viral hepatitis. However, greater recognition by national governments and the international community of the urgency to comprehensively tackle both HBV and HCV are still needed. In all countries, strategic plans and policy goals need to be translated into resources and concrete actions, with national governments at the helm, to enable a sustainable response to the rising burden of hepatitis B and C in all countries.